0067 An Anatomic Substrate for GABAergic Processes to Suppress Active Sleep and Promote Wakefulness in the Nucleus Pontis Oralis. (27th May 2020) - Zhang, J; Sampogna, S; Xi, M; Fung, S J; Tobin, C; Chase, M H
Abstract: Introduction: Our previous electrophysiologic data have provided compelling evidence that GABAergic processes in the nucleus pontis oralis (NPO) play a critical role in the generation and maintenance of wakefulness as well as active (REM) sleep (AS). We therefore hypothesized that one of the neuronal mechanisms of GABA actions in the NPO to promote wakefulness and suppress AS is due to a direct GABAergic inhibition of NPO neurons that generate AS (AS-generator neurons). However, the anatomical substrate for this inhibition is undetermined. Accordingly, the present study was undertaken to examine whether there is any direct interaction between GABAergic neurons and glutamatergic AS-generator neurons in the NPO. Methods: Adult cats were deeply anesthetized and perfused transcardially. The brainstem containing the NPO was removed, postfixed and cut into 15 μm coronal sections with a Reichert-Jung cryostat. The sections were incubated with a mixture of a rabbit polyclonal antibodies against glutamine and GABA following the procedure of double fluorescence immunohistochemistry. Results: There was a large number of neuronal somata labeled by anti-glutamine antibody and terminals labeled by anti-GABA antibody in the NPO. These glutamine-positive neurons were medium to large, multipolar cells (> 20 μm), which resemble glutamatergic, AS-generator neurons that have been previously identified in the NPO. Specifically, majority of glutamatergic neuronal somata were closely apposed by multiple GABAergic terminals, indicating that AS-generator neurons in the NPO receive direct GABAergic inputs. Conclusion: The present results demonstrate that a direct connection exists between glutamatergic AS-generator neurons and GABAergic processes in the NPO. These data provide the anatomical evidence which supports our hypothesis that the pontine GABAergic control of wakefulness and active sleep is partially mediated via GABAergic processes project to NPO AS-generator neurons that suppress the activity of these cells. Support: NS092383